Association between systemic immune-inflammation index and atopic dermatitis: a cross-sectional study of NHANES 2001–2006 - Ding, Qike; Lin, Lihong; Li, Xiaoting; Xie, Xiaoping; Lu, Tao (Frontiers in Medicine, 2024)
Background: While several studies have noted a higher SII correlates with multiple diseases, research on the association between SII and atopic dermatitis remains limited. Our cross-sectional study seeks to examine the association between SII and atopic dermatitis among outpatient US adults.: This compensatory cross-sectional study utilized NHANES data from 2001-2006 cycles, conducting sample-weighted multivariate logistic regression and stratified analysis of sub-groups.Results: Higher levels of SII were positively associated with an increased risk of atopic dermatitis in adults with BMI <30 (OR, 1.44; 95% CI, 1.10-1.90) (P= 0.010).Conclusions: Our findings suggested SII higher than 330 x 10 9 /L was positively associated with a high risk of atopic dermatitis in US adults with BMI <30. To our knowledge, this is the first study focused on the risk of higher SII on atopic dermatitis in the outpatient US population. Currently, there are differences in the standards used to diagnose atopic dermatitis across countries, and our study may have implications.